A Study Comparing 0.025% Topical Tretinoin Versus 4% Retinol Peel and 10% Retinol Peel in the Management of Acanthosis Nigricans - Shreya Srinivasan; C Balakumaran; G Sukanya; N Ashok Kumar; A Sakthi Megalai; Aswin Senthilvel (Indian Dermatology Online Journal)
Background: Acanthosis nigricans (AN) presents a significant challenge for dermatologists, as it is a common condition yet often proves resistant to treatment. Aim and Objective: To compare the effects of 0.025% topical tretinoin, 4% retinol peel, and 10% retinol peel, in the management of AN of neck using Acanthosis Nigricans Area Severity Index (ANASI) score. Patients and Methods: Patients with AN of neck were recruited to the study with due consideration to the inclusion criteria and were divided into 3 groups based on the treatment administered which was either 0.025% topical tretinoin, 4% retinol peel, or 10% retinol peel. The patients were followed-up every 2 weeks up to 8 weeks with ANASI score and Likert scale. Results: All the groups demonstrated statistically significant improvement but participants in the topical group achieved a slightly better reduction, with a mean ANASI score of 10 at final follow-up, followed by 10% retinol and 4% retinol peel with a mean ANASI score of 12 and 11, respectively. Overall, though 4% retinol peel group had the least reported side effects, patient satisfaction score was found to be higher among the participants in the topical group. Limitations: Small sample size and allocation of patients to different treatment groups was not randomized. Conclusion: Among the three groups, topical tretinoin group showed better response when compared to 4% and 10% retinol peels and, as such, can be a preferred mode of treatment since it is also cost effective over the more expensive chemical peels. Thus, in the era of chemical peels and lasers, topical treatment with retinoids still holds good.